2-(3-Methyl-2-oxoquinoxalin-1-yl)-N-(4-methylphenyl)acetamide - Mohcine Missioui; Abdulsalam Alsubari; Joel T. Mague; El Mokhtar Essassi; Youssef Ramli (IUCrData, 2023)
The quinoxaline moiety in the title molecule, C18H17N3O2, is not quite planar and the p-tolyl group is rotationally disordered over two nearly equally populated sets of sites. In the crystal, N—H...O and C—H...O hydrogen bonds form chains extending along the b-axis direction. Due to the disorder of the p-tolyl rings, short C...C distances are observed between adjacent chains.